HDAC5–LSD1 axis regulates antineoplastic effect of natural HDAC inhibitor sulforaphane in human breast cancer cells. Issue 6 (20th April 2018) - Cao, Chunyu; Wu, Hao; Vasilatos, Shauna N.; Chandran, Uma; Qin, Ye; Wan, Yong; Oesterreich, Steffi; Davidson, Nancy E.; Huang, Yi
Abstract : Our recent studies have shown that cross‐talk between histone deacetylase 5 (HDAC5) and lysine‐specific demethylase 1 (LSD1) facilitates breast cancer progression. In this work, we demonstrated that regulatory activity at −356 to −100 bp promoter element plays a critical role in governing HDAC5 transcription. By using DNA affinity precipitation and mass spectrometry, we identified a group of factors that bind to this element. Among these factors, Upstream Transcription Factor 1 (USF1) was shown to play a critical role in controlling HDAC5 transcription. Through screening a panel of epigenetic modifying drugs, we showed that a natural bioactive HDAC inhibitor, sulforaphane, downregulated HDAC5 transcription by blocking USF1 activity. Sulforaphane facilitated LSD1 ubiquitination and degradation in an HDAC5‐dependent manner. A comparative microarray analysis demonstrated a genome wide cooperative effect of HDAC5 and LSD1 on cancer‐related gene expression. shRNA knockdown and sulforaphane inhibition of HDAC5/LSD1 exhibited similar effects on expression of HDAC5/LSD1 target genes. We also showed that coordinated cross‐talk of HDAC5 and LSD1 is essential for the antitumor efficacy of sulforaphane. Combination treatment with sulforaphane and a potent LSD1 inhibitor resulted in synergistic growth inhibition in breast cancer cells, but not in normal breast epithelial cells. Furthermore, combined therapy with sulforaphane and LSD1 inhibitor exhibited superior inhibitory effect on MDA‐MB‐231 xenograft tumor growth. Taken together, our work demonstrates that HDAC5–LSD1 axis is an effective drug target for breast cancer. Inhibition of HDAC5–LSD1 axis with sulforaphane blocks breast cancer growth and combined treatment with LSD1 inhibitor improves the therapeutic efficacy of sulforaphane. Abstract : What's new? The post‐translational modification of histones through acetylation serves an important role in the regulation of gene expression. Histone deacetylases (HDACs) are a critical component of this system. This study sheds light on regulatory mechanisms of HDAC5 transcription and shows that sulforaphane, an HDAC inhibitor, suppresses HDAC5 expression through downregulation of upstream transcription factor 1 (USF1). USF1 downregulation in turn destabilizes lysine‐specific demethylase 1 (LSD1) protein in breast cancer cells. The findings suggest that targeting the HDAC5–LSD1 axis through combined sulforaphane and LSD1 inhibitor treatment could be an effective approach to enhancing antineoplastic efficacy of epigenetic agents against breast cancer.